DUA MATA MEMANDANG KARHUTLA (ANALISIS FRAMING PEMBERITAAN KARHUTLA DI THE STAR DAN KOMPAS.COM MODEL ROBERT N. ENTMAN) - Chelsea Andriany; Novelia Wijayanti; Miletresia Miletresia; Kho Gerson Ralph Manuel (SEMIOTIKA: Jurnal Komunikasi, 2019)
ABSTRACTForest and Land Fire Disasters (KARHUTLA) recurrently occur in Indonesia every year, especially in the dry season. In addition to numerous places in Indonesia, neighboring country like Malaysia also got affected by the after effects of KARHUTLA: smog. As a result, Smog has greatly been a concerned issue of both Malaysian and Indonesian media. While both of the media reporting on the same issue, fundamentally both media have different perspectives representing both countries; none of them wants to be held as solely responsible party that triggered the disaster. News framing that has been applied by the media to speak for their subjective objectivity shapes a distinct perception of reality among their audiences as a consequence. This is what makes researchers interested in analyzing more deeply the description and phenomenon of KARHUTLA reporting by using a descriptive qualitative research method. This study uses the Robert N. Entman framing analysis model as a tool to dissect media coverage of KARHUTLA issues from their respective perspectives. On the basis of research conducted by researchers, the online news portal The Star Malaysia and Kompas.com Indonesia were established as research subjects. While the object of this research is the news related to KARHUTLA. The results of the framing analysis show that there are media efforts to shape the perception of the reality of the states of Indonesia and Malaysia that are "accusing" each another of the KARHUTLA disaster and “making scapegoat” for the responsibility for it. Consequently, the image of the Indonesian nation was damaged by the contents of media coverage.Keywords: KARHUTLA ; framing analysisABSTRAKBencana Kebakaran Hutan dan Lahan (KARHUTLA) sudah kerap kali terjadi di wilayah Indonesia setiap tahunnya, khususnya pada musim kemarau. Kabut asap yang merupakan dampak dari KARHUTLA juga dirasakan oleh negara tetangga, yaitu Malaysia. Hal ini mengundang perhatian media Malaysia maupun Indonesia untuk menyoroti isu kabut asap yang kian meresahkan kedua negara tersebut. Isi pemberitaan dibingkai oleh media dari beberapa sudut pandang berita yang merepresentasikan Indonesia dengan Malaysia yang saling melempar tanggung jawab atas dampak kabut asap kebakaran hutan. Pembingkaian tersebut menciptakan persepsi realitas yang berbeda. Hal inilah yang membuat peneliti tertarik untuk menelaah secara lebih dalam gambaran dan fenomena tentang pemberitaan KARHUTLA dengan menggunakan metode penelitian pendekatan deskriptif kualitatif. Penelitian ini menggunakan framing analysis model Robert N.Entman sebagai alat untuk membedah pemberitaan media yang mengulas permasalahan KARHUTLA dari perspektif masing – masing. Atas dasar riset yang dilakukan peneliti, portal berita online The Star Malaysia dan Kompas.com Indonesia ditetapkan sebagai subjek penelitian. Sedangkan yang menjadi objek penelitian ini adalah pemberitaan terkait KARHUTLA. Hasil framing analysis memperlihatkan adanya upaya media untuk membentuk persepsi realitas negara Indonesia dan Malaysia yang saling “tuding-menuding” perihal tanggung jawab bencana KARHUTLA. Akibatnya image bangsa Indonesia diciderai oleh isi pemberitaan media.Kata Kunci: KARHUTLA; Analisis Framing